Solar Surface Magnetic Field Simulation from 2010 to 2024 and Anomalous Southern Poleward Flux Transport in Cycle 24 - Ruihui Wang; Jie Jiang; Yukun Luo (The Astrophysical Journal, 2025)
The solar surface magnetic field is fundamental for modeling the coronal magnetic field, studying the solar dynamo, and predicting solar cycle strength. We perform a continuous simulation of the surface magnetic field from 2010 to 2024, covering solar cycle 24 and the ongoing cycle 25, using the surface flux transport model with assimilated observed active regions (ARs) as the source. The simulation reproduces the evolution of the axial dipole strength, polar field reversal timing, and magnetic butterfly diagram in good agreement with Solar Dynamics Observatory/Helioseismic and Magnetic Imager observations. Notably, these results are achieved without incorporating radial diffusion or cyclic variations in meridional flow speed, suggesting their limited impact. Poleward surges of the following polarity typically dominate throughout the cycle, but in the southern hemisphere during cycle 24, they are limited to a short period from 2011 to 2016. This anomalous pattern arises from intermittent AR emergence, with about 46% of the total unsigned flux contributed by ARs emerging during Carrington rotations 2141–2160 (2013 September–2015 February). These ARs show a strong active longitude at Carrington longitudes 200°−260° and a weaker one at 80°−100°. After 2016, poleward migrations of leading-polarity flux become dominant, despite most ARs following Joy’s and Hale’s laws. This reversal is likely due to prolonged intervals between AR emergences, which allow the leading-polarity flux to distribute across a broad latitude range before cancellation by subsequent ARs. These findings highlight the importance of the temporal interval of AR emergence in driving the flux transport pattern.